Chemical synthesis and mechanism of a natural product from endolichenic fungus with a broad-spectrum anti microorganism activity - Zhou, Xuan; Wang, Ming-Yi; Cao, Qian-Ping; Yang, Ze; Meng, Qing-Feng; Fu, Shao-Bin (Frontiers in Microbiology, 2023)
(1) Background: The increasing bacterial resistance has posed a serious threat to human health, prompting the need for the discovery of novel structurally-featured natural products with promising biological activities for drug research. Endolichenic microbes have been proven to be a fertile source for the production of various chemical components, and thus have become an intensive focus for the exploration of natural products. To this end, the secondary metabolites of an endolichenic fungus were investigated in order to excavate potential biological resources and antibacterial natural products. (2) Methods: The antimicrobial products were isolated from the endolichenic fungus using various chromatographic methods, and the antibacterial and antifungal activities of the compounds were evaluated by the broth microdilution method in vitro. The antimicrobial mechanism was preliminarily discussed by measuring the dissolution of nucleic acid and protein, as well as the activity of Alkaline phosphatase (AKP). Chemical synthesis of the active product compound 5 was also performed, starting from commercially available 2,6-dihydroxybenzaldehyde via a sequence of transformations, including methylation, the addition of propylmagnesium bromide addition on formyl group, the oxidation of secondary alcohol, and the deprotection of methyl ether motif. (3) Results: Among the nineteen secondary metabolites of the endolichenic fungus Daldinia childiae, compound 5 showed attractive antimicrobial activities on ten of the fifteen tested pathogenic strains, including Gram-positive bacteria, Gram-negative bacteria, and fungus. The Minimum Inhibitory Concentration (MICs) of compound 5 for Candida albicans 10213, Micrococcus luteus 261, Proteus vulgaris Z12, Shigella sonnet, and Staphylococcus aureus 6538 was identified as 16 μg/mL, whereas the Minimum Bactericidal Concentration (MBCs) of other strains were 64 μg/mL. Compound 5 could dramatically inhibit the growth of S. aureus 6538, Proteus sp., and C. albicans 10213 at the concentration of MBC, probably by affecting the permeability of the cell wall and membrane. These results enriched the library of active strains and metabolites resources of endolichenic microorganisms. The chemical synthesis of the active compound was also performed by four steps, providing an alternative pathway to the excavation of antimicrobial agents.